2020
DOI: 10.7717/peerj.9282
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer patients can benefit from 5-alpha-reductase inhibitor treatment: a meta-analysis

Abstract: Background The efficacy and safety of 5α-reductase inhibitors (5ARIs) in treating prostate cancer (PCa) have not been fully determined. We performed a meta-analysis to evaluate the effectiveness and safety of 5ARIs for PCa patients. Methods A comprehensive literature search of online databases was conducted to obtain comparative studies exploring the effectiveness and safety of 5ARIs in treating PCa up to October 2019. Summarized odds ratio s (OR s) or hazard ratio s (HR s) were calculated to compare the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This meta-analysis observed no statistically significant difference between high-grade prostate cancer diagnoses and 5-ARI use (RR 0.98, 95% CI: 0.67-1.43, I 2 =75%). Furthermore, they observed no statistically significant difference in prostate cancer-specific mortality rates between the 5-ARI exposure arm and the control arm, a finding supported by three other meta-analyses, along with multiple other publications (42,43,(45)(46)(47)(48)(49)(50)(51).…”
Section: Prostate Cancermentioning
confidence: 72%
“…This meta-analysis observed no statistically significant difference between high-grade prostate cancer diagnoses and 5-ARI use (RR 0.98, 95% CI: 0.67-1.43, I 2 =75%). Furthermore, they observed no statistically significant difference in prostate cancer-specific mortality rates between the 5-ARI exposure arm and the control arm, a finding supported by three other meta-analyses, along with multiple other publications (42,43,(45)(46)(47)(48)(49)(50)(51).…”
Section: Prostate Cancermentioning
confidence: 72%
“…Given the long-term follow-up data and clear evidence of benefit in terms of risk reduction of lowrisk prostate cancer, these drugs might warrant consideration for this indication in selected men, particularly those with lower urinary tract symptoms [26]. A recent systematic review [27] using over 2000 patients from 10 studies showed a statistically significant decrease in prostate cancer risk associated with use of 5-ARI drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Finasteride and dutasteride, two primary 5α-reductase inhibitors, have been reported with various side effects during long-term administration such as sexual adverse effects, erectile dysfunction, and loss of libido [ 20 , 21 , 22 ]; these drugs decreased ejaculation by 3.4 to 15.8 percent in men [ 23 ]. In addition, the use of 5α-reductase inhibitors for BPH can be the reason for prostate cancer and the risk of all-cause mortality [ 24 , 25 ]. Moreover, tamsulosin, an α 1A -adrenergic receptor blocker, may increase the risk of dementia in older men with BPH via its selectivity relative to α 1A -adrenoceptors in the brain [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%